2022
DOI: 10.1038/s41467-021-27710-w
|View full text |Cite
|
Sign up to set email alerts
|

Observation of localized magnetic plasmon skyrmions

Abstract: Optical skyrmions have recently been constructed by tailoring vectorial near-field distributions through the interference of multiple surface plasmon polaritons, offering promising features for advanced information processing, transport and storage. Here, we provide experimental demonstration of electromagnetic skyrmions based on magnetic localized spoof plasmons (LSP) showing large topological robustness against continuous deformations, without stringent external interference conditions. By directly measuring… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…Localized spoof-plasmon devices were designed to generate such optical target skyrmions in the magnetic field with controllable radial kπ twist degree. Such quasipartcles are also confined to a deep-subwavelength volumes [45]. Intriguingly, the near-equidistant space-coiling meta-structure of the spoof-plasmon device can be tailored into arbitrary shapes, demonstrating flexible skyrmionic textures robust with arbitrary shapes (Fig.…”
Section: Optical Quasiparticles Beyond Skyrmions and Meronsmentioning
confidence: 99%
See 2 more Smart Citations
“…Localized spoof-plasmon devices were designed to generate such optical target skyrmions in the magnetic field with controllable radial kπ twist degree. Such quasipartcles are also confined to a deep-subwavelength volumes [45]. Intriguingly, the near-equidistant space-coiling meta-structure of the spoof-plasmon device can be tailored into arbitrary shapes, demonstrating flexible skyrmionic textures robust with arbitrary shapes (Fig.…”
Section: Optical Quasiparticles Beyond Skyrmions and Meronsmentioning
confidence: 99%
“…Dynamics of such skyrmionic SPP standing wave can be observed using photoemission electron microscopy [44]. Spoof localized SPP were also reported to generate skyrmion-like structures for the fields in a coiled metal films or metallic multifold structure acting as a resonator [45,46] but the topological protection needs to be further investigated. SPP field-skyrmions have the topological texture limited to Néel-type topology.…”
Section: Skyrmions In Evanescent Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be highly desirable if the shapes of low-frequency IFSs can be customized at will, then we could control the EM wave propagation behavior in a relatively broader bandwidth. It is well known that metallic wire medium [4,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], such as disconnected wire arrays, can exhibit the strong spatial dispersion (nonlocal effect) even in long-wavelength limit [25,26]. By incorporating two or more sets of metallic meshes, one can engineer the density of states at quasistatic limit [28,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, researchers [33] found that the global connectivity of these metallic meshes can introduce a momentum shift of the low-frequency index ellipsoid away from the zero k-point. Recently, wire medium again attracted the attention of researchers, since it could serve as a new design degree of freedom to tailor the low-frequency dispersion [34][35][36][37] and associated wave properties [38][39][40] of MMs.…”
Section: Introductionmentioning
confidence: 99%